Crisis lawyering : effective legal advocacy in emergency situations - Brescia, Ray; Stern, Eric K. (New York : New York University Press, 2021)
'Crisis Lawyering' shines a light on the emerging field of law dedicated to responding to and resolving the crises of the twenty-first century.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Due process of law -- United States; Justice, Administration of -- United States; Law; Laws of specific jurisdictions & specific areas of law